Intention to Adopt Sustainable Energy : Applying the Theory of Planned Behaviour Framework - Srivastava, Chetan; Mahendar, G. (Indian Journal of Marketing, 2018)
Numerous factors influence the adoption intention of the household solar energy products. This research paper studied these factors by adopting the theory of planned behaviour framework. The primary data for this paper was collected using the structured questionnaires which were administered to 250 respondents from Telangana State, out of which 165 were usable. The data thus collected was analyzed using structured equation modeling (SEM) and analysis of moment squares (AMOS). The results of the study aligned with the theory of planned behaviour framework. It was found that apart from perceived benefits, demographic variables played a dominant role in intention for adoption of solar energy products. The outcomes of the study indicated that (a) perceived benefit had a significant positive relationship with customer attitude; (b) perceived risk had a negative relation to attitude; (c) normative beliefs and moral obligation had a significant positive relationship with subjective norms; (d) control force and control belief had a significant positive relationship with perceived behavioral control; (e) customers' attitude, subjective norms, andÂ perceived behavioral control had a significant positive relationship with customers' purchase intentions. Though, the past research highlighted the adoption of solar energy with different variables, but in isolation. However, the current study utilized all the major constructs of the theory of planned behaviour in the conceptual framework. This study contributes to the literature on solar energy from the customers' perspective. In addition, the proposed framework could be the basis for future research in the field of consumer behaviour in the solar-energy sector.